Laparoscopic transabdominal cerclage in a patient with a complete septate uterus and duplicated cervices - Alzamora Schmatz, Maria C.; Sridhar, Shobha; Billow, Megan (Fertility and sterility, 2025)
Cervical insufficiency is a significant cause of second-trimester loss and preterm birth. Transabdominal cerclage is indicated after failed transvaginal cerclage or anatomical factors that make a vaginal approach technically difficult—such as müllerian anomalies, prior cervical surgery, or cervical duplication. In patients with müllerian anomalies undergoing a cerclage placement, it is critical to properly identify the anatomy for surgical planning and patient counseling of the cerclage method. To describe transabdominal cerclage indications and surgical technique and to illustrate a needleless laparoscopic abdominal cerclage placement in a patient with a complete septate uterus and duplicated cervices and important related considerations. Case report. This case describes a 33-year-old G2P0201 female, with a history of undergoing a loop electrosurgical excision procedure and longitudinal vaginal septum resection, and who was previously misdiagnosed with a didelphic uterus and duplicated cervices. She had a failed history-indicated transvaginal cerclage placed around the cervix connected to the gravid hemicavity during her second pregnancy and was referred to our practice for transabdominal cerclage placement. A preoperative magnetic resonance imaging scan was performed. (The patient(s) included in this video gave consent for publication of the video and posting of the video online including social media, journal website, scientific literature websites [such as PubMed, ScienceDirect, Scopus, etc.] and other applicable sites.) Needleless laparoscopic transabdominal cerclage. Preoperative workup, imaging, and surgical technique. Magnetic resonance imaging scan revealed a complete septate uterus with duplicated cervices. A needleless laparoscopic transabdominal cerclage was placed after careful dissection of the uterine vessels at the level of the internal cervical os and creation of a tunnel medial to them. Nonabsorbable, braided polyester suture was used. Transabdominal cerclage is a feasible alternative in patients with congenital uterine anomalies, as a transvaginal approach might increase the risk of failure. Accurate diagnosis through advanced imaging, multidisciplinary consultation, and individualized surgical planning are key to optimizing reproductive outcomes. [Display omitted]